Implementation of Complete Systematic Land Registration Fee (PTSL) Determination at City/District Level - Ardo Yoga Pradana; Achmad Sulchan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
This study aims to examine the policy for setting a Complete Systematic Land Registration (PTSL) fee at the central government level and the implementation of a Complete Systematic Land Registration (PTSL) fee determination at the Regency/City level. The research method in this thesis uses a normative juridical method and the research specification is descriptive analysis with the type of data based on primary and secondary data. Based on the results of observations and studies of laws and regulations related to the object of research, it shows that the PTSL costing policy has been regulated by the central government through a Joint Decree of 3 Ministers in which PTSL costs are categorized according to the region. Local governments in determining policies related to PTSL costing, their implementation must still refer to central policies so that policy synchronization continues. Regions that set costs in accordance with the SKB rules can immediately socialize the implementation of PTSL. Meanwhile, regions that determine the costs of PTSL themselves, through a policy-making mechanism and their determination must be regulated in writing through regional/village regulations. Suggestions from the results of this study. The implementation of PTSL needs to be socialized more massively, the government must ensure that there are no illegal fees, and if there are costs that exceed the provisions, a written determination is made and socialized to the public.